The Optimization of a Novel Hydrogel—Egg White-Alginate for 2.5D Tissue Engineering of Salivary Spheroid-Like Structure - Yuli Zhang; Hieu M. Pham; Jose G. Munguia-Lopez; Joseph M. Kinsella; Simon D. Tran (Molecules, 2020)
Hydrogels have been used for a variety of biomedical applications; in tissue engineering, they are commonly used as scaffolds to cultivate cells in a three-dimensional (3D) environment allowing the formation of organoids or cellular spheroids. Egg white-alginate (EWA) is a novel hydrogel which combines the advantages of both egg white and alginate; the egg white material provides extracellular matrix (ECM)-like proteins that can mimic the ECM microenvironment, while alginate can be tuned mechanically through its ionic crosslinking property to modify the scaffold’s porosity, strength, and stiffness. In this study, a frozen calcium chloride (CaCl2) disk technique to homogenously crosslink alginate and egg white hydrogel is presented for 2.5D culture of human salivary cells. Different EWA formulations were prepared and biologically evaluated as a spheroid-like structure platform. Although all five EWA hydrogels showed biocompatibility, the EWA with 1.5% alginate presented the highest cell viability, while EWA with 3% alginate promoted the formation of larger size salivary spheroid-like structures. Our EWA hydrogel has the potential to be an alternative 3D culture scaffold that can be used for studies on drug-screening, cell migration, or as an in vitro disease model. In addition, EWA can be used as a potential source for cell transplantation (i.e., using this platform as an ex vivo environment for cell expansion). The low cost of producing EWA is an added advantage.